Genomics studies on plantation tree species in Sarawak - Ho Wei, Seng; Pang Shek, Ling; Lai, Pei Sing; Tiong, Shing Yiing; Phui, Seng Loi; Liew, K.S.; M., Nurfaizah; B.L., Tchin; Ismail, Jusoh; Tawan, C.S; Petrus, Bulan; Julaihi, Abdullah (2010)
Rapid socio-economic changes in the world are having profound impacts on all sectors, including forestry. The increase in global demand for wood requires increase in forest productivity. The alternative is to farm trees in plantations composed of fast-growing species with short rotation cycles (6–8 y). The rationale is that natural forests at the most produce about 3 m3 ha y-1 of commercial timber, whereas plantations can produce annually from 10 m3 ha y-1 of hardwoods to 30 m3 ha-1 of softwoods and thus, decrease the effects of human pressure on our ecosystems while increasing the competitiveness of Sarawak’s forest industry. This is in line with the state government’s aspiration to establish one million hectares of planted forests by year 2020 to meet the increasing demand from both domestic and international markets for raw materials. It is estimated at least 30 million seedlings are required for annual planting or reforestation programmes. In this regard, forest genomics research will help respond to the need to develop adequate tools that enable us to produce quality planting materials that are of faster growth, high yield and high wood quality, and also adapted to local conditions, so that we may achieve economic benefits of great significance. Realizing the need, we have centred our research on the development of tools via biotechnological innovations for tree breeders. Over the years, we have successfully developed: 1) simple sequence repeat (SSR) 173 DNA markers specific for identifying the genetic make-up of two fastgrowing indigenous tree species, i.e. kelampayan and sawih; 2) the ‘Touch-incubate-PCR’ approach for preparing plant tissues for high throughput genotyping, and 3) a kelampayan tree transcriptome database (NcdbEST aka CADAMOMICS) for wood formation. These tools will greatly facilitate the selection of quality planting materials for planted forest development in Sarawak as well as long-term tree improvement activities by integrating genomics into our breeding programme via association mapping. The overall benefit of genomics application to tree improvement programme will be in terms of greater certainty in the outcome of results, specifically the performance of the forest plantations, as well as the savings in time and cost in the production and supply of quality planting materials.